Artificial higher order neural networks for economics and business - Zhang, Ming, 1949 July 29- (Information Science Reference, 2009)
"This book is the first book to provide opportunities for millions working in economics, accounting, finance and other business areas education on HONNs, the ease of their usage, and directions on how to obtain more accurate application results. It provides significant, informative advancements in the subject and introduces the HONN group models and adaptive HONNs"--Provided by publisher.